Effect of microwave drying of the spines of book blocks on the quality of printed materials - Havenko, Svitlana; Korobchynskyi, Maksym; Yordan, Hanna; Kadyliak, Myroslava; Bernatsek, Volodymyr (Eastern-European Journal of Enterprise Technologies, 2017)
Based on the main provisions of the theory of heat and mass transfer, we examined the kinetics of natural and microwave drying of the spines of book blocks. The existence of three periods of drying is proven: a period of warming the block (when the moisture content of paper reduces along a certain curve); a period of constant rate (when moisture content reduces by the law of a straight line); a period of falling rate (when there is a redistribution of moisture removal and it becomes uniform for all layers, thereby ensuring product quality). Based on the graph-analytic analysis of curves of the intensity of microwave drying and mathematical modeling, we demonstrated relationship between the time of drying, temperature, and the type of paper. Thus, an increase in relative air humidity by 20 % results in a decrease in the intensity of drying by about 2 times (for the blocks made from chalk overlay paper) and by 1.5 times (for the blocks made from offset paper). An increase in air temperature by 10 °C results in a reduction in the drying time of blocks made from chalk overlay paper by about 1.5 minutes, and of the blocks made from offset paper – by 1 minute. We established optimal modes of microwave drying of book blocks (3–5 minutes at a temperature of 40 °C). We have proven a positive effect of microwave drying on the performance indicators of books: resistance of blocks to the sign-alternating loads on the spine, maximal effort of breaking the blocks and pulling sheets out of the blocks. The study that we conducted is important to ensure quality in the book manufacturing process, as well as strength of book structure for its intensive use by readers